Bioactive Peptides: A Complementary Approach for Cancer Therapy - Khademi, Nazanin; Mehrnia, Nariman; Esmailpour Roshan, Mojtaba (Asian Pacific Journal of Cancer Care, 2024)
Background: The relentless pursuit of effective cancer treatments has led researchers to explore bioactive peptides as a complementary approach to cancer therapy. These peptides, which can be of natural or synthetic origin, are not only identified as potent therapeutic agents but also exhibit significant diagnostic capabilities. The review aims to summarize the properties, classification, and mechanisms of action of these natural peptides on different cancer cell lines, suggesting their potential as safer and more effective cancer treatments. Objective: To provide an in-depth exploration of bioactive peptides derived from natural sources, revealing their anticancer properties and theoretical models that explain their actions. The review also addresses the complexities of ACP production and classification and sheds light on their potential as less harmful and more precise alternatives to conventional cancer therapies. Method: The review includes a comprehensive analysis of the literature on bioactive peptides, focusing on their origin, properties, classification, and mechanisms of action. It examines various theories that explain the effect of bioactive peptides on cancer cells and discusses the natural sources of these peptides, their production processes, and classification into different types of ACPs. Findings: The review identifies a range of bioactive peptides with anticancer properties from various sources, including animals, plants, fungi, and marine organisms. These peptides act through diverse mechanisms, such as membrane disruption, apoptosis induction, and immune system modulation. The review provides a detailed account of the peptides’ effects on different cancer cell lines and their potential therapeutic applications. Discussion and Conclusion: The review concludes that bioactive peptides offer a promising avenue for cancer therapy, with the potential to revolutionize treatment landscapes. It emphasizes the need for further research to fully realize the therapeutic potential of these peptides and their role in the future of cancer treatment. The review also highlights the importance of understanding the structure-function relationship of bioactive peptides to enhance their therapeutic efficacy and reduce systemic toxicity.